2018
DOI: 10.18203/2349-3291.ijcp20184182
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance pattern of uropathogens in urinary tract infections in children at State Referral Hospital, Falkawn, Mizoram, India

Abstract: Background: Analysing antibiotic susceptibility pattern of uropathogens help to overcome the therapeutic difficulties created by the rising anti-microbial resistant bacteria and guides in choosing appropriate antibiotics. Hence, we aimed at evaluating the uropathogens causing urinary tract infections and study their antibiograms.Methods: Midstream urine samples were collected, cultured and appropriate biochemical tests were performed for proper identification of urinary tract pathogens in State Referral Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This is a rather alarming finding for the northeastern region of India because it indicates faster dissemination of antibiotic resistance genes had occurred among the bacterial population. A study conducted by the state referral hospital in Falkawn, Mizoram, showed the emergence of a large number of MDR strains in this region [10]. Our study, which focused on two areas, Lunglei and Aizawl, found a high incidence of antibiotic resistance in Gram-negative bacteria to the last-resort antibiotics carbapenem, colistin and tigecycline.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…This is a rather alarming finding for the northeastern region of India because it indicates faster dissemination of antibiotic resistance genes had occurred among the bacterial population. A study conducted by the state referral hospital in Falkawn, Mizoram, showed the emergence of a large number of MDR strains in this region [10]. Our study, which focused on two areas, Lunglei and Aizawl, found a high incidence of antibiotic resistance in Gram-negative bacteria to the last-resort antibiotics carbapenem, colistin and tigecycline.…”
Section: Discussionmentioning
confidence: 48%
“…In the northeast regions, in the states of Mizoram, Tripura, Nagaland and Meghalaya, the prevalence of carbapenem resistance were found to be below 5% due to less developed healthcare and the comparably reduced amounts of carbapenems used in these regions [10]. Based on this information, this study was conducted to assess the emergence of Gramnegative bacteria in Mizoram that are carbapenem-resistant, as well as to detect the presence of carbapenemase genes in the clinical isolates collected from two hospitals in the region.…”
Section: Introductionmentioning
confidence: 99%
“…or ampicillin 1-2 g orally or i.v. (especially infection due to enterobacter) or a cephalosporin (19). Follow up urine culture is recommended after 2 weeks of therapy.…”
Section: Treatment Of Upper Utimentioning
confidence: 99%